Familial Pancreatic Cancer: The Case for Prophylactic Pancreatectomy in Lieu of Serial Screening and Shared Decision Making - Mazen E. Iskandar; Michael G. Wayne; Justin G. Steele; Avram M. Cooperman (Case Reports in Oncological Medicine)
At-risk family members with familial pancreatic cancer (FCaP) face uncertainty regarding the individual risk of developing pancreatic cancer (CaP) and whether to choose serial screening or prophylactic pancreatectomy to avoid CaP. We treated 2 at-risk siblings with a history of FCaP, congenital hepatic fibrosis (CHF), and jaundice secondary to a bile duct stricture. In one, a pancreaticoduodenal resection was done and in the second a total pancreatectomy. Malignancy was not present, but extensive pancreatic intraepithelial neoplasia (PanIn) 2 was present throughout both pancreata. The clinical course and literature review are presented along with the previously unreported association of CHF and CaP.